Analisis Harga Jual pada Pendapatan Petani Kopi - Sintia Sahna Sari Febriani; Jawoto Nusantoro; Elmira Febri Darmayanti (Expensive: Jurnal Akuntansi dan Keuangan, 2026)
This study is research that uses qualitative apporach with a qualitative descriptive method that aims to analyze selling prices, other factors and strategies that can increase the income of coffee farmers in Bonglai Village, Banjit District, Way Kanan Regency. The population in this study is 697 respondents. The sampling technique in this study uses the slovin formula and sets the significance level at 10% so that a sample of 87 respondents is obtained. Data analysis is carried out through several stages, namely data processing which includes data reduction, data presentation, and verification. To test the validity of the data, several methods are used, including credibility tests, dependency tests, transferability tests, and confirmability tests. The analysis tool used is the Guttman scale. The results of this study show that selling prices, and other factors such as production and climate change as well as land productivity strategies and processing technology have a great impact on the income level of coffee farmers in Bonglai Village, Banjit District, Way Kanan Regency.